Models versus radiosondes in the free atmosphere: A new detection and attribution analysis of temperature. Issue 6 (28th March 2013) - Lott, F. C.; Stott, P. A.; Mitchell, D. M.; Christidis, N.; Gillett, N. P.; Haimberger, L.; Perlwitz, J.; Thorne, P. W.
Abstract: [1] This analysis revisits detection and attribution of free atmosphere temperatures from radiosondes, almost a decade after previous studies. Since that time, data sets have not only become longer, but understanding of observational uncertainty has vastly improved. In addition, a coordinated set of experiments exploring the effects of human and natural forcings on past climate change has been made with a new generation of climate models. These advances allow a much more thorough analysis of the effects of modeling and observational uncertainty on attribution results than previously possible. Observational uncertainty is explored using multiple radiosonde reconstructions including those with ensembles of realizations exploring the effects of processing choices. Modeling uncertainty is explored by calculating multiple fingerprints of natural influence (from changes in solar irradiance and volcanic aerosols) and of human influence (due to greenhouse gases and due to the effects of combined anthropogenic forcings including stratospheric ozone depletion). With increased confidence over previous studies, human influences (both greenhouse gas and other anthropogenic forcings) have been detected in spatiotemporal changes in free atmosphere temperature from 1961 to 2010, irrespective of whether the full atmospheric column (30–850 hPa) is examined or purely the troposphere, with stratospheric ozone depletion dominating the cooling that has been observed in the lower stratosphere. Thus the advances of the last decade yield increased confidence that anthropogenic influences have made a substantial contribution to the evolution of free atmosphere temperatures. Key Points: Human influences detected in changes in free atmosphere temperature 1961‐2010 Latest radiosonde observations and climate simulations confirm previous reports Robust to observational uncertainty and to inclusion or absence of stratosphere